Severe thyroiditis induced by sintilimab monotherapy in a patient with non-small cell lung cancer: a case report and literature review - Zhao, Xiaolin; Wang, Xiaoyu; Liu, Surui; Cheng, Pian; Chen, Jinjuan; Liu, Jie (Frontiers in Immunology, 2025)
Thyroid dysfunction is a common immune-related adverse event (irAE) associated with immune checkpoint inhibitors (ICIs) that target PD-1, PD-L1, and CTLA-4. Nevertheless, the incidence of severe cases, defined as grade 3 or higher, remains rare. This report presents a detailed case study of severe thyroiditis in a patient with non-small cell lung cancer (NSCLC) who developed grade 3 thyroiditis following a single cycle of sintilimab monotherapy. The clinical presentation in this patient was remarkable for its early onset, occurring one week after the initiation of sintilimab therapy, and for its severe manifestations. During hospitalization, a prompt and accurate differential diagnosis was performed. Sintilimab treatment was discontinued, and the patient was promptly started on high-dose glucocorticoids, with a tapering schedule implemented as the condition improved or reached Common Terminology Criteria for Adverse Events (CTCAE) grade 1 or lower. The patient subsequently developed overt hypothyroidism, necessitating the initiation of thyroxine replacement therapy. Furthermore, we provide a comprehensive review of the mechanisms and risk factors associated with thyroid dysfunction immune-related adverse events (TD-irAEs). It is imperative for clinicians to meticulously monitor the clinical symptoms exhibited by patients. For those presenting with symptoms, prompt diagnosis and appropriate symptomatic management are essential. Additionally, regular thyroid function testing is recommended for high-risk patients, and we advocate for the assessment of baseline levels of thyroid peroxidase antibodies (TPOAb) and thyroglobulin antibodies (TGAb) prior to initiating ICI treatment.